(untitled) (Minerva, 2019)
0>TT<0>This article starts from the opinion of the modern scholars who have relegated Cornelius Nepos to the condition of second or third category author to refute them responding to the data offered about him by those who were his contemporaries, those who knew his work with posteriority and those who have studied it or used its data. <0 0>Mediante el análisis de los textos, nos proponemos la revisión de la figura del escritor latino a través de sus lectores y del público destinatario de sus obras.<0>By means of the analysis of these texts, we propose to review the Latin writer’s figure through his readers and the public of his works. <0